A five‐gene methylation signature predicts overall survival of patients with clear cell renal cell carcinoma. Issue 12 (30th October 2021) - Jing, Xiao; Xu, Gang; Gong, Yu; Li, Junlong; LingfengWu,; Zhu, Wei; He, Yi; Li, Zhongyi; Pan, Shouhua
Abstract: Background: In this study, we aimed to screen methylation signatures associated with the prognosis of patients with clear cell renal cell carcinoma (ccRCC). Methods: Gene expression and methylation profiles of ccRCC patients were downloaded from publicly available databases, and differentially expressed genes (DEGs)‐differentially methylated genes (DMGs) were obtained. Subsequently, gene set enrichment and transcription factor (TF) regulatory network analyses were performed. In addition, a prognostic model was constructed and the relationship between disease progression and immunity was analyzed. Results: A total of 23 common DEGs‐DMGs were analyzed, among which 14 DEGs‐DMGs were obtained with a cutoff value of PCC < 0 and p  < 0.05. The enrichment analysis showed that the 14 DEGs‐DMGs were enriched in three GO terms and three KEGG pathways. In addition, a total of six TFs were shown to be associated with the 14 DEGs‐DMGs, including RP58, SOX9, NF‐κB65, ATF6, OCT, and IK2. A prognostic model using five optimized DEGs‐DMGs which efficiently predicted survival was constructed and validated using the GSE105288 dataset. Additionally, four types of immune cells (NK cells, macrophages, neutrophils, and cancer‐associated fibroblasts), as well as ESTIMATE, immune, and stromal scores were found to be significantly correlated with ccRCC progression (normal, primary, and metastasis) in addition to the five optimized DEGs‐DMGs. Conclusion: A five‐gene methylation signature with the predictive ability for ccRCC prognosis was investigated in this study, consisting of CCNB2, CDKN1C, CTSH, E2F2, and ERMP1 . In addition, potential targets for methylation‐mediated immunotherapy were highlighted. Abstract : Objective: This study aimed to screen the methylation signatures related to the prognosis of patients with clear cell renal cell carcinoma (ccRCC). Methods: The gene expression and methylation profilings were downloaded, followed by the differentially expressed gene (DEG)‐differentially methylated genes (DMGs) were obtained. Then the enrichment analysis and transcript factor (TF) regulatory network were performed. In addition, the prognosis model was constructed, and the relation between disease progression and immunity was analyzed. Results: A total of 23 common DEG‐DMGs was analyzed, among which 14 DEG‐DMGs were obtained with the cutoff value of PCC <0 and p  < 0.05. The enrichemnt analysis shown that the 14 DEG‐DMGs enriched in 3 GO terms and 3 KEGG pathways. In addition, a total of six TFs were obtained related to the 14 DEG‐DMGs, including RP58, SOX9, NFKAPPAB65, ATF6, OCT, IK2. Besides, a prognostic model from five ptimized DEG‐DMGs effectively predicted survival was constructed, and validated in the GSE105288 dataset. Moreover, four immune cells (including NK cell, Macrophage, Neutrophil, Cancer associated fibroblast) and ESTIMATE score, immune score and stromal score were found significantly correlated with the ccRCC progression (normal, primary, and metastasis), and five ptimized DEG‐DMGs correlated with these four immune cells and ESTIMATE score, immune score and stromal score. Conclusion: Five Methylation signatures with the predictive ability of ccRCC prognosis were screened in this study, including CCNB2, CDKN1C, CTSH, E2F2, ERMP1. Also, the potential targets for methylation‐mediated immunotherapy were highlighted.